Advanced Assessment : interpreting findings and formulating differential diagnoses - Goolsby, Mary Jo; Grubbs, Laurie, 1951- (Philadelphia, PA : F.A. Davis Company, 2019)
Step by step, you'll hone your ability to perform effective health assessments, obtain valid data, interpretthe findings, and recognize the range of conditions that can be indicated by specific findings to reach an accuratedifferential diagnosis. You'll have coverage of 170 conditions and symptoms across the lifespan at your
Includes bibliographical references and index
1 13
Keywords: Diagnosis, Differential; Nurse practitioners; Nursing assessment; Nursing Assessment -- methods